Widefield Two-photon Excitation Without Scanning: Live Cell Microscopy With Hightime Resolution And Low Photo-bleaching - Nor Zaihana Abdul Rahman; Rumelo Amor; Alison McDonald; Johanna Trägårdh; Gillian Robb; Louise Wilson; John Dempster; William Bradshaw Amos1; Trevor J. Bushell; Gail McConnell (Amor et al, 2024)
We demonstrate fluorescence imaging by two-photon excitation without scanning in biological specimens as previously described by Hwang and co-workers, but with an increased field size and with framing rates of up to 100 Hz. During recordings of synaptically-driven Ca2+ events in primary rat hippocampal neurone cultures loaded with the fluorescent Ca2+ indicator Fluo-4 AM, we have observed greatly reduced photo-bleaching in comparison with single-photon excitation. This method, which requires no costly additions to the microscope, promises to be useful for work where high time-resolution is required.